Agricultural production and use in Rajshahi, Bangladesh: Crop, homestead, livestock, and fish cultivation and use - Laing, Alison; Kamal, Mustafa; Faisal, Asif Al; Karki, Saral; Druti, Baishakhee Pashari; Nandi, Ravi; Sarker, Palash; Kumar, Neha; Kishore, Avinash; Gathala, Mahesh; Krupnik, Timothy J. (TAFSSA, 2023)
The TAFSSA district food systems assessment aims to provide a reliable, accessible and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management in Bangladesh, India, and Nepal. It is intended to be a multi-year assessment. This data note summarizes data collected in February March 2023 to describe what smallholder farmers are cultivating and what they do with the farm products produced. It is part of a pack of data notes that, together, provide a holistic picture of the food system in the district. The survey methodology is briefly summarized in the penultimate page of this data note.